2008
DOI: 10.1111/j.1753-4887.2008.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of lycopene metabolites: implications for cancer prevention

Abstract: While early studies focused on the potential roles in health and disease of provitamin A carotenoids, such as beta-carotene, research over the past decade has provided a framework for our understanding of the functions of non-provitamin A carotenoids such as lycopene, especially in regards to its association with a reduced risk of a number of chronic diseases, including cancer. Recent data suggests that lycopene metabolites may possess specific biological activities on several important cellular signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(132 citation statements)
references
References 129 publications
(313 reference statements)
1
129
1
1
Order By: Relevance
“…High selfreported intakes of tomato and tomato products, and of dietary lycopene (a carotenoid compound) are associated with lower risk for CVD [5,6]. Lycopene is one of the most potent antioxidants and the most predominant carotenoid in human plasma and it is assumed to be one of the active compounds on the health benefits of tomato [7]. While the epidemiological evidence indicates a consistent association between tomato products and/or lycopene and lower CVD risk [5,6], the effect of nutritional interventions on tomato products and lycopene have been studied only recently and their efficacy on improving vascular function remains to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…High selfreported intakes of tomato and tomato products, and of dietary lycopene (a carotenoid compound) are associated with lower risk for CVD [5,6]. Lycopene is one of the most potent antioxidants and the most predominant carotenoid in human plasma and it is assumed to be one of the active compounds on the health benefits of tomato [7]. While the epidemiological evidence indicates a consistent association between tomato products and/or lycopene and lower CVD risk [5,6], the effect of nutritional interventions on tomato products and lycopene have been studied only recently and their efficacy on improving vascular function remains to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Accumulating evidence suggests the potentiality of LP for targeting cancer therapy as an anticancer agent. However, the extreme instability and poor bioavailability of LP may limit its application in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed to determine the antioxidant capacity of several carotenoids concluded that this capacity depends on the structure of each specific carotenoid; increasing in the following order: lycopene > β-cryptoxanthin > α-carotene > β-carotene > zeaxanthin > lutein [27]. Several in vitro studies have indicated that lycopene is a powerful antioxidant, a quencher of singlet oxygen, and has the ability to scavenge free radicals [36]. In the meantime, β-carotene eliminates free radicals, neutralizes singlet oxygen and protects DNA from its mutagenic activity [37].…”
Section: Evaluation Of the Individual And Combinedmentioning
confidence: 99%